2000
DOI: 10.1021/ie000270q
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of Nitrogen Oxides in Columns Equipped with Low-Pressure Drops Structured Packings

Abstract: The absorption of nitrogen oxides was investigated experimentally in a column equipped with HelieR structured packing for different values of operative conditions (NO x inlet concentration, specific gas, and liquid flow rate). The experimental data were compared with the absorption efficiency predicted by three models, the first obtained by the open literature and the others developed in this work. Some conclusions about the relative importance of the different masstransfer mechanisms involving the absorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Mechanism.The mechanism of SO 2 and NO removal in the bubbling reactor involves numerouse parallel and consecutive reactions. From the results of ion chromatograph,it was found that the samples from reactor included SO 3 2 ‾, I -, SO 4 2 ‾, NO 2 ‾, NO 3 ‾and few HSO 3 ‾,It is assumed that, in acidic medium I 2 mainly works as agent to oxidize SO 2 into SO 3 ,and oxidize NO into NO 2 ,Further absorption of NO 2 is believed to take place hydrolysis of N 2 O 3 or N 2 O 4 [6,7]. The oxidative absorption of SO 2 can be expressed as:…”
Section: Resultsmentioning
confidence: 99%
“…Mechanism.The mechanism of SO 2 and NO removal in the bubbling reactor involves numerouse parallel and consecutive reactions. From the results of ion chromatograph,it was found that the samples from reactor included SO 3 2 ‾, I -, SO 4 2 ‾, NO 2 ‾, NO 3 ‾and few HSO 3 ‾,It is assumed that, in acidic medium I 2 mainly works as agent to oxidize SO 2 into SO 3 ,and oxidize NO into NO 2 ,Further absorption of NO 2 is believed to take place hydrolysis of N 2 O 3 or N 2 O 4 [6,7]. The oxidative absorption of SO 2 can be expressed as:…”
Section: Resultsmentioning
confidence: 99%
“…Some mature and efficient technologies have been developed to absorb nitrogen oxide by water, dilute nitric acid, ionic liquids, or activated carbon to prepare nitric acid again. [75][76][77] Therefore, our method of oxidative upgrading of waste polystyrene plastics by nitric acid has high feasibility in practical applications (Fig. 14).…”
Section: Industrial Application Analysismentioning
confidence: 99%
“…Considerable modeling of various pieces of equipment of a nitric acid plant has been carried out and a modeling, simulation and optimization strategy has been proposed in a recent work by Chatterjee and Joshi [7]. In this work as well as practically by all the studies reported in the published literature [8][9][10][11][12][13][14][15][16][17][18], the depletion of aqueous nitrous acid in the absorber and the bleacher in a nitric acid plant has not been adequately modeled.…”
Section: Introductionmentioning
confidence: 99%